Challenges in accessing routinely collected data from multiple providers in the UK for primary studies: Managing the morass. (2018) - Lugg-Widger, Fiona V; Angel, Lianna; Cannings-John, Rebecca; Hood, Kerenza; Hughes, Kathryn; Moody, Gwenllian; Robling, Michael
No abstract available